MANAJEMEN LAYANAN BIMBINGAN DAN KONSELING DALAM MENINGKATKAN PRESTASI AKADEMIK SISWA DI MADRASAH TSANAWIYAH NEGERI (MTsN) 1 JOMBANG - Ahmad Marom; Sri Haryanto; Muhtar Sofwan Hidayat (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to explore the strategies used by ustadz (Islamic teachers) to instill religious character values in santri at TPQ Al-Masyhur Selokromo, Leksono, Wonosobo. Using a qualitative descriptive method, data were collected through interviews, observations, and documentation with the TPQ head and ustadz as key informants. The findings show that ustadz applied various strategies including role modeling, habituation, positive reinforcement, contextual learning, and collaboration with parents. These strategies resulted in improved student behavior, regular religious practices, and active participation in TPQ activities. Supporting factors include a religious environment, teacher dedication, structured programs, and parental support. However, challenges such as students' diverse backgrounds, limited study time, minimal parental involvement, and lack of facilities remain.